PENGARUH EARNING PERSHARE (EPS), DEBT TO EQUITY RATIO (DER), FIRM SIZE, DAN KEPEMILIKAN MANAJERIAL TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR SEKTOR KONSUMSI YANG TERDAPAT DI BEI TAHUN 2019 - 2022 - Marbun, Ignes Santalia; Lilia , Wirda; Munte , Judika Sukmawati; Syaefudin, Fanesa Isalia Minanda (Mount Hope Economic Global Journal, 2024)
This study aims to see how the relationship between variables either individually or together. Observations of this study used purposive sampling with partial test (T test), simultaneous test (F test), classical assumption test, and Adjusted R square test. The test results for this observation are earnings per share (EPS), debt to equity ratio (DER), and firm size have a significant effect on return on equity (ROE) while managerial ownership has no but significant effect on return on equity (ROE ). With the adjusted R square result of 85.7% and influenced by other variables of 14.3%. So the overall results of earnings per share (EPS), debt to equity ratio (DER), firm size, managerial ownership have a simultaneous effect on manufacturing companies in the consumer goods sector listed on the Indonesia stock exchange in 2019 - 2022.